Preparation and properties of novel activated carbon doped with aluminum oxide and silver for water treatment - Rashad Al-Gaashani (16936965) (2021)
Novel activated carbon (AC) composite materials, namely AC doped with aluminum oxide (Al2O3) and AC doped with Al2O3 and silver (Ag) nanoparticles, have been prepared via a one-step thermal decomposition method. The developed composite materials were used to study the adsorptive removal of molybdenum (Mo) and arsenic (As) from contaminated water. Several techniques, including X-Ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron spectroscopy (SEM), energy dispersive X-Ray spectroscopy (EDS), and thermal gravimetric analysis (TGA), were used to characterize the synthesized materials. TGA results show that the material is very stable and decay starts only above 450 °C. The effects of pH on the adsorptive removal of As and Mo on AC-Al2O3 have also been studied. The prepared AC-Al2O3 material showed 94% removal of total As at pH of 6% and 97% removal of Mo at pH 2. The pollutants removal is due to electrostatic attraction and ligand exchange adsorption mechanisms. It was also found that the novel AC-Al2O3-Ag composite materials exhibit notable antibacterial properties towards both Gram-negative (Escherichia coli) and Gram-positive (Bacillus subtilis) bacteria. Other Information Published in: Journal of Alloys and Compounds License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jallcom.2020.158372